IMPLEMENTASI MANAJEMEN MUTU PADA INDUSTRI PENANGKAPAN IKAN (Implementation of Quality Management on Fishing Industry) - Tri Wiji Nurani; Sugeng Hari Wisudo; Mohammad Imron (Bogor Agricultural University, 2012)
ABSTRAKThe Indonesian government has already paid high attention to the quality assurance of fishery products. It can be seen from the legislation and policies that have been established. In a Ministry of Marine Affari Regulation (Kepmen KP 01/MEN/2007) clearly stated that the quality assurance requirements and food safety of fishery products, start from the production, processing and distribution. Meanwhile, fisherman understanding of the qualityof fish product is still low. This study was conducted to assess the implementation of Kepmen KP 01/MEN/2007 in the fishing industry. Analysis of the the implementation of the quality elements refers to â€œThe Aplication of the guidelines of PMMT based on the conception HACCPâ€ (Dirjen Perikanan Tangkap, 1999). The results showed that the implementation of quality management system according Kepmen KP 01/MEN/2007 on fishing vessels in Palabuhanratu fishing port wasstill dificult to implement. In small vessels, factors that wascause the difficulty of implementation wasthe limited space of fishing boat and knowledge of fisherman. While in the long line and trolling, structural requirements, the feasibility of the ship and regristation of ship has already implemented, but related to hygiene and handling of fish on board have not implemented properly.Key words: fishing industry, implementation of quality management, Kepmen 01/MEN/2007, PPNPalabuhanratu——-ABSTRAKKeberpihakan pemerintah terhadap jaminan mutu pada produk hasil perikanan sudah cukup tinggi, terlihat dari peraturan perundang-undangan ataupun kebijakan-kebijakan yang telah ditetapkan. Pada Kepmen 01/MEN/2007 tersirat dengan jelas persyaratan jaminan mutu dan keamanan pangan produk-produk perikanan, mulai dari proses produksi, pengolahan dan distribusi. Sementara itu pemahaman mengenai mutu ikan di tingkat nelayan sebagai pelaku utama industri penangkapan ikan masih rendah. Penelitian ini dilakukan untuk melihat sejauhmana implementasi dari Kepmen 01/MEN/2007 pada industri penangkap ikan.Analisis kesesuaian implementasi unsur-unsur manajemen mutudilakukan dengan mengacu pada â€Pedoman Penerapan PMMT Berdasarkan Konsepsi HACCPâ€ (Dirjen Perikanan Tangkap 1999). Hasil penelitian menyatakan bahwa penerapan atau implementasi manajemen mutu sesuai Kepmen No.01/Men/2007pada kapal penangkap ikan di PPN Palabuhanratu masih sulit untuk diimplementasikan. Pada kapal berukuran kecil, keterbatasan ruang dan keterbatasan pengetahuan ABK, menjadi faktor sulitnya implementasi, sPersyaratan struktur dan kelayakan kapal serta registrasi sudah diimplementasikan pada kapallongline dan pancing tonda, gistra.Namun terkait dengan higiene kapal dan penanganan masih belum diimplementasikan dengan baik.Kata kunci: industri penangkapan